Pembuktian Hukum Adat Sebagai Solusi Alternatif Penyelesaian Kasus di Masyarakat - Abdul Kadir Sabaruddin (Fakultas Hukum Universitas Mulawarman, 2010)
The verification through custom law may be found in the community where they determine the defendant as guilty or not through “Shroud Pledge”. This pledge is often conducted when the crime committed by the defendant is difficult to be verified. The verification through custom law, especially through “Shroud Pledge”, is an alternative solution which is more effective to solve any cases in the community.